Está mudando ou tá mudado? : a expressão do item estar no continuum fala/escrita - Pinheiro, Frederico Pitanga (2024)
In the Brazilian Portuguese scene, both in spoken and written modality, the item estar can be expressed under the configuration of two variants: without morphophonological reduction (está, estou, estão, estava, estavam, estaria, estariam, estivesse, estivessem etc.) and with morphophonological reduction (tá, tô, tão, tava, tavam, taria, tariam, tivesse, tivessem etc.). In the light of sociofunctionalism (CEZARIO; MARQUES; ABRAÇADO, 2016; GÖRSKI; TAVARES, 2013; TAVARES, 2013; TAVARES; GÖRSKI, 2015), through the interface between linguistic variation and grammaticalization (GÖRSKI; TAVARES, 2017; NARO; BRAGA, 2000; POPLACK, 2011), this thesis aims, fundamentally, to investigate the alternation between the full and reduced forms of the item estar in a set of 188 Monica's Gang comic books from the 1970s, 1980s, 1990s. 2000s and 2010s (ZANELLATO, 2021) and to compare the results obtained by Pinheiro (2019), which investigated this very phenomenon through 46 sociolinguistic interviews conducted with informants from Vitória/ES that make up part of the PortVix database (TESCH; YACOVENCO, 2022; YACOVENCO, 2002; YACOVENCO et al., 2012). The analyses processed by the GoldVarb X software (SANKOFF; TAGLIAMONTE; SMITH, 2005) indicate that, in the capixaba speaking community, the expression of the item estar is an almost completed case of shift, considering that reduced variants are used in a semi categorical proportion (96,9%). The Monica’s Gang comic books, on the other hand show, over the course of five decades, a more even distribution, with the full forms (61,2%) standing out when compared to reduced forms (38,8%). Nevertheless, it is worth noting that the frequency of the reduced forms has gradually increased over time. In the 1970s, there was a little over 5% of reduction, meanwhile, in the 2010s, the reduced forms already represented more than half of the estar uses (56,4%). The statistical multivariate analysis indicates that both in the speech of Vitória/ES and in the writing of the analyzed comic books, the reduced forms of the item estar are favored for their more grammaticalized functions, at the same time, the source function and the less grammaticalized functions inhibit the reductions. Moreover, the singular structures and the present indicative, less marked contexts when compared to plural structure and further tenses, moods and verbal nominal forms, equally regulate the reductions in a favorable way. Concerning the characters of Monica’s Gang comic books, a clear division between the rural and urban axes is noted, with the figures connected with the rural context strongly favoring the reduced forms, while the figures that present urban traits behave in an 17 intermediate way or inhibit reductions. However, it is worth noting that the opposition urban vs. rural is not evidentiated in real uses of the day-by-day speech. By comparing the speech of Vitória, the capital city of Espírito Santo and an urbanized environment, with the speech of the rural area of Santa Leopoldina, a city in the interior of the state, it is ascertained that the proportion of reduction of the estar item in these two communities is very alike: 96,9% and 99% respectively. This leads to the conclusion that reduced forms of estar, in the writing of Monica’s Gang comic books, are used as one more resource to constitute the stigmatized speech of Chico Bento and other characters of the rural environment. Finally, in what concerns the textual genres sociolinguistic interviews and comic books, the factor that allows a reduced manifestation of estar seems to be their oral discursive conceptions. This line of thought gains more power when observing that the textual genres e-mail and newscast, both based on the writing, inhibit the reductions of the item estar (PINHEIRO, 2016). Based on these results, it is still not possible to answer with a complete certainty the title-bearing question of this thesis: after all, is the expression of the item estar changing, or has it already changed? Even though the speech of Vitória/ES and the speech of Santa Leopoldina/ES show a clear context of almost complete change and, in the Monica’s Gang comic books the reduced estar forms have gained a considerable space, more contexts of use of the modes of language need to be investigated in order to obtain a better overview of this variable phenomenon